2014
DOI: 10.1002/etep.1929
|View full text |Cite
|
Sign up to set email alerts
|

Generation expansion planning for Tamil Nadu: a case study

Abstract: Summary Generation expansion planning (GEP) is a highly constrained, non‐linear optimization problem. The selection of the best expansion alternative for long‐term planning horizon is commonly referred as GEP problem. In this paper, the GEP problem is solved for Tamil Nadu, an Indian state for the period of 30 years from 2012 to 2041 using a state‐of‐the‐art computer model Wien Automatic System Planning IV package. In the year 2012, the peak load for Tamil Nadu was approximately 12 000 MW and had a peak load s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Multistage multiobjective GEP problem aims in finding a group of best decision vectors over a planning period that minimizes the capital investment, operating costs, and CO 2 emitted to the environment for appropriate constraints. The forecasted peak demand till the year 2028 for Tamil Nadu power system is shown in Table A.1 . The technical and economic data of candidate plants, pumped storage power plant, and existing plants are presented in Tables A.2 and A.3 respectively…”
Section: Formulation Of Mmgep Problemmentioning
confidence: 99%
“…Multistage multiobjective GEP problem aims in finding a group of best decision vectors over a planning period that minimizes the capital investment, operating costs, and CO 2 emitted to the environment for appropriate constraints. The forecasted peak demand till the year 2028 for Tamil Nadu power system is shown in Table A.1 . The technical and economic data of candidate plants, pumped storage power plant, and existing plants are presented in Tables A.2 and A.3 respectively…”
Section: Formulation Of Mmgep Problemmentioning
confidence: 99%
“…The dynamic behavior of 150‐MW HDGT was analyzed using this model, and the responses were validated . Careful modeling and control of HDGT plants are required to avoid inevitable shutdown in grid connected operation . In order to improve the dynamic and steady‐state response of higher‐order HDGT plants, attempts were made to develop proportional‐integral‐derivative (PID) controller and soft computing techniques–based controllers such as neural network, fuzzy logic, and neuro‐fuzzy technique …”
Section: Introductionmentioning
confidence: 99%
“…Integration of renewable energy plants with an advanced gas turbine can be a viable solution for most of the stability issues . Recent survey on biomass gasifier power plants and a study of generation expansion plan for Tamilnadu, a southern state of India, suggested that the huge potential renewable sources can be converted into useful energy by proper modelling and implementing suitable control strategy . Gas turbine plant may cause severe instability problems under load fluctuation and may lead to an inevitable plant shutdown .…”
Section: Introductionmentioning
confidence: 99%